(NrOMANTI^ESKAQ GARMONIQ I EE KRIZIS W tRISTANE wAGNERAs - (N|(B.(NkURTs; (Ng(B. (NbALTERs (NPEREWOD^IKs ((NmOSKWAs (NmUZYKAs, 1975)
(NrOMANTI^ESKAQ GARMONII I EE KRIZIS W tRISTANE wAGNERA |RISTA kURTA(B-(NKRUPEJ[EGO ZARUBEVNOGO MUZYKOWEDA hh WEKA(B-(NPRINADLEVIT K ^ISLU KLASSI^ESKIH NAU^NYH TRUDOW(B.s
Keywords: (NmONOGRAFIQs